AKUNTABILITAS KINERJA PEMERINTAH PROVINSI DKI JAKARTA TAHUN 2015–2019 - Samara, Ilmaa -; Yuwono, Teguh - (Journal of Politic and Government Studies, 2020)
Accountability is one of the key elements of sustaining Good Governance. Therefore, a Government Agency is said to be able to implement Good Governance if this key element is considered good by the standard that the performance targets that have been determined are based on the needs of the community, as well as the budget that has been allocated in the previous fiscal year.This study uses a mixed methodology with data collection techniques, namely interviews, data or archives, and questionnaires. After that, the analysis uses triangulation theory, sources and methods. The results show that the increase in the value of performance accountability is not always directly proportional to the substantive performance, although in some sectors it is directly proportional, namely the increase in the value of performance is in accordance with the results felt by the public. Therefore, the government is trying to improve substantive performance with administrative work through innovation, strengthening leadership and strengthening top-down and bottom-up.These efforts such as innovation, strengthening leadership and strengthening top-down and bottom-up have been able to improve the performance accountability represented by the performance accountability system value of provincial government agencies in Jakarta in the last 5 (five) years, namely 2015–2019.Researchers recommend to improve the implementation of the efforts made to level up the score of SAKIP, and not only the score of SAKIP but the increasing of substantive performance run by the DKI Jakarta Provincial Government.